Direct Health Care Cost and Work Incapacity Related to Complex Regional Pain Syndrome in Switzerland: A Retrospective Analysis from 2008 to 2015. Issue 8 (8th March 2019) - Scholz-Odermatt, Stefan Markus; Luthi, François; Wertli, Maria Monika; Brunner, Florian
Abstract: Objective: First, to determine the number of accident-related complex regional pain syndrome (CRPS) cases from 2008 to 2015 and to identify factors associated with an increased risk for developing CRPS. Second, to analyze the duration of work incapacity and direct health care costs over follow-up periods of two and five years, respectively. Design: Retrospective data analysis. Setting: Database from the Statistical Service for the Swiss National Accident Insurances covering all accidents insured under the compulsory Swiss Accident Insurance Law. Subjects: Subjects were registered after an accident between 2008 and 2015. Methods: Cases were retrospectively retrieved from the Statistical Service for the Swiss National Accident Insurances. Cases were identified using the appropriate International Classification of Diseases, 10th Revision, codes. Results: CRPS accounted for 0.15% of all accident cases. Age, female gender (odds ratio [OR] = 1.53, 95% confidence interval [CI] = 1.47–1.60), and fracture of the forearm (OR = 38, 95% CI = 35–42) were related to an increased risk of developing CRPS. Over five years, one CRPS case accumulated average insurance costs of 86, 900 USD and treatment costs of 23, 300 USD. Insurance costs were 19 times and treatment costs 13 times the average costs of accidents without CPRS. Within the first two years after the accident, the number of days lost at work was 20 times higher in patients with CRPS (330 ± 7 days) than in patients without CRPS (16.1 ± 0.1 days). Two-thirds of all CRPS cases developed long-term work incapacity of more than 90 days. Conclusion: CRPS is a relatively rare condition but is associated with high direct health care costs and work incapacity.